Root-Shoot Signaling crosstalk involved in the shoot growth promoting action of rhizospheric humic acids. (2nd April 2016) - Olaetxea, Maite; Mora, Verónica; García, Andrés Calderin; Santos, Leandro Azevedo; Baigorri, Roberto; Fuentes, Marta; Garnica, María; Berbara, Ricardo Luis Louro; Zamarreño, Angel Maria; Garcia-Mina, Jose M.
ABSTRACT: Numerous studies have shown the ability of humic substances to improve plant development. This action is normally reflected in an enhancement of crop yields and quality. However, the mechanisms responsible for this action of humic substances remain rather unknown. Our studies have shown that the shoot promoting action of sedimentary humic acids is dependent of its ability to increase root hydraulic conductivity through signaling pathways related to ABA, which in turn is affected in roots by humic acids in an IAA-NO dependent way. Furthermore, these studies also indicate that the primary action of humic acids in roots might also be physical, resulting from a transient mild stress caused by humic acids associated with a fouling-cleaning cycle of wall cell pores. Finally the role of alternative signal molecules, such as ROS, and corresponding signaling pathways are also discussed and modeled in the context of the above-mentioned framework.